2006
DOI: 10.1039/b516658f
|View full text |Cite
|
Sign up to set email alerts
|

Reaction dynamics simulations of the identity SN2 reaction H2O + HOOH2+→ H2OOH++ H2O. Requirements for reaction and competition with proton transfer

Abstract: Despite the fact that the transition structure of the gas phase S(N)2 reaction H(2)O + HOOH(2)(+)--> HOOH(2)(+)+ H(2)O is well below the reactants in potential energy, the reaction has not yet been observed by experiment. Variational transition state RRKM theory reveals a strong preference for the competing proton transfer reaction H(2)O + HOOH(2)(+)--> H(3)O(+)+ HOOH due to entropy factors. Born-Oppenheimer reaction dynamics simulations confirm these results. However, by increasing the collision energy to aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The k(E i , J ) was computed with the Beyer-Swinehart algorithm 60 to determine the number of states implemented in the SuperRRKM program. [62][63][64][65][66] The calculated values of E* as well as the geometries, energies and vibrational frequencies are available in the ESI. These thermal contributions were calculated at 298 K and rotational effects were not considered ( J = 0).…”
Section: Rrkm Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The k(E i , J ) was computed with the Beyer-Swinehart algorithm 60 to determine the number of states implemented in the SuperRRKM program. [62][63][64][65][66] The calculated values of E* as well as the geometries, energies and vibrational frequencies are available in the ESI. These thermal contributions were calculated at 298 K and rotational effects were not considered ( J = 0).…”
Section: Rrkm Calculationsmentioning
confidence: 99%
“…This procedure to compute E i has been successfully applied to estimate the product distributions of several gas-phase reactions. [62][63][64][65][66] The calculated values of E* as well as the geometries, energies and vibrational frequencies are available in the ESI. †…”
Section: Rrkm Calculationsmentioning
confidence: 99%
“…The rate constants for the two elimination channels can then be estimated by RRKM theory if statistical behavior is assumed for these reactions. This type of approach has been used in the past to determine relative efficiencies of gas-phase S N 2 reactions, to describe the outcome of ionic reactions that proceed through a double minimum well surface energy or neutral processes through long-lived intermediates, and to estimate the branching ratios of gas-phase ionic and neutral reactions …”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…tential energy surfaces (PES) and the structure of species and transition states (TS). [19][20][21][22][23][24][25][26][27] Activation-strain analyses [28] of the anionic substitution reactions between halides and halomethanes [29] have shown that the S N 2 barrier decreases as the highest-occupied molecular orbital (HOMO) of the nucleophile becomes a better electron donor, that is, as the basicity of the nucleophile becomes stronger, because of a more stabilizing interaction between nucleophile and substrate. Likewise, a weaker bond between carbon and the leaving group (CÀLG) also leads to a lower S N 2 barrier because the energetic strain associated with such a weaker bond is less destabilizing.…”
Section: Introductionmentioning
confidence: 99%